The relationship of growth differentiation factor 15 with some biochemical parameters in cardiovascular disease patients in Babylon City - Hiba Resheed Behayaa; Zinah Abbass Ali; Seenaa Badr Mohammed; Suhayr A. Alqaysi (Medical Journal of Babylon)
Abstract Background: Cardiovascular disease (CVD) is one of the reasons of mortality in the world. In the developing world, deaths from CVD have been increasing. Growth differentiation factor 15 (GDF15) is about cachexia, CVD, and a lot of inflammatory diseases. GDF15 is very low in most tissues, except the placenta (in healthy conditions), which expresses GDF15 in high levels. Though in cardiovascular damage, the level of GDF15 may rise, the natural effects of GDF15 may vary according to the stage of the disease. Objective: The objective of the study was the valuation of GDF15 level in the serum of patients with CVD in Babylon City and to check whether there was a link between age, body mass index, lipid profile, insulin resistance, adiponectin and C-reactive protein with GDF15. Materials and Methods: GDF15 was assessed in 80 Iraqi subjects; 40 were diagnosed with CVD and 40 subjects who appear healthy were considered for this study. The age ranged between 41 and 73 years for patients and control was considered for this study. Enzyme-linked immunosorbent assay technique was used for GDF15 estimation. Results: The results suggested that the serum levels of GDF15 and homeostatic model assessment for insulin resistance displayed a non-significant difference among studied groups (P > 0.05), whereas total cholesterol, high-density lipoprotein, triglyceride, adiponectin, and C-reactive protein appeared to have a significant difference among studied groups (P < 0.05). In contrast, the current study observed a non-significant (P > 0.05) association for GDF15 with all the clinical and biochemical parameters measured in this study. Conclusion: The study concluded that among the patients with CVD, the level of GDF15 revealed a non-significant relationship with the disease.